Siblings of Disabled Peoples' Attitudes Toward Prenatal Genetic Testing and Disability: A Mixed Methods Approach - Friedman, Carli; Owen, Aleksa L (Disability Studies Quarterly, 2016)
We used the phenomenon of prenatal genetic testing to learn more about how siblings of disabled people understand prenatal genetic testing and social meanings of disability. By interweaving data on siblings' conscious and unconscious disability attitudes and prenatal testing with siblings' explanations of their views of prenatal testing we explored siblings' unique relationships with disability, a particular set of perspectives on prenatal genetic testing, and examined how siblings' decision-making processes reveal their attitudes about disability more generally. In doing so we found siblings have both personal and broad stakes regarding their experiences with disability that impact their views.